Penatalaksanaan Fisioterapi Anak Cerebral Palsy Spastik Hemiplegi Sinistra: Studi Kasus Enam Sesi Terapi Latihan PNTC - Robbani Khoirul Bariyyah; Amalia Solichati Rizqi; Yudha Wahyu Putra (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Cerebral palsy (CP) is a permanent and non-progressive disorder of movement and posture development caused by injury to the developing brain that may result in motor, sensory, postural, and functional impairments in children. Children with spastic hemiplegic cerebral palsy commonly experience spasticity, trunk instability, impaired postural control, and limitations in functional activities that require long-term physiotherapy management. This study aimed to describe the physiotherapy management and clinical response of a child with Spastic Hemiplegic Cerebral Palsy Sinistra following exercise therapy intervention. This case study was conducted at PNTC Colomadu Clinic from January 10 to January 24, 2026, involving six physiotherapy sessions over a two-week period. The interventions included myofascial release, back extensor muscle massage, trunk stretching and mobilization, oral motor stimulation, sitting control exercises, gait training, and standing exercises. Evaluation was performed using the Modified Ashworth Scale (MAS), Pediatric Evaluation of Disability Inventory (PEDI), Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), Communication Function Classification System (CFCS), Eating and Drinking Ability Classification System (EDACS), Visual Function Classification System (VFCS), and Short Sensory Profile (SSP). The results showed that no objective clinical improvement was observed in spasticity, motor function, functional ability, or sensory responses after six therapy sessions. However, the patient demonstrated stable functional conditions without further deterioration during the intervention period. Exercise therapy may contribute to maintaining functional capacity, preventing secondary complications, and supporting long-term sensorimotor rehabilitation in children with severe neurological involvement.